2018
DOI: 10.1523/jneurosci.0860-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoglycan Alpha Mitigates Neuromuscular Junction Decline in Aged Mice by Stabilizing LRP4

Abstract: During aging, acetylcholine receptor (AChR) clusters become fragmented and denervated at the neuromuscular junction (NMJ). Underpinning molecular mechanisms are not well understood. We showed that LRP4, a receptor for agrin and critical for NMJ formation and maintenance, was reduced at protein level in aged mice, which was associated with decreased MuSK tyrosine phosphorylation, suggesting compromised agrin-LRP4-MuSK signaling in aged muscles. Transgenic expression of LRP4 in muscles alleviated AChR fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 101 publications
5
75
0
Order By: Relevance
“…4a-d). In line with previous reports 37, 44 , we observed lower density of postsynaptic AChRs in cross sections from EDL muscles of 30mCON (trend) as well as 9mTSCmKO mice, (Fig. 4e).…”
Section: Resultssupporting
confidence: 93%
“…4a-d). In line with previous reports 37, 44 , we observed lower density of postsynaptic AChRs in cross sections from EDL muscles of 30mCON (trend) as well as 9mTSCmKO mice, (Fig. 4e).…”
Section: Resultssupporting
confidence: 93%
“…A paper recently reported reduced levels of Lrp4 protein expression and MuSK activation in muscle of aged mice, suggesting impaired MuSK-mediated signaling due to loss of Lrp4 protein. Indeed, the authors demonstrated that transgenic expression of Lrp4 in skeletal muscle from the embryonic stage alleviates NMJ denervation and improves neuromuscular transmission and muscle strength in aged mice ( Zhao et al., 2018 ). Also, they found that Lrp4 interacts with sarcoglycan α (SGα) and demonstrated that intramuscular injection with an AAV serotype 9 vector expressing SGα fused with green fluorescent protein (GFP) (AAV9-SGα-GFP) at 22.5 months of age resulted in increased NMJ innervation, neuromuscular transmission, and muscle strength as compared with the AAV9-GFP-treated controls in 24-mo mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, CMS is not a degenerative disorder like aging but a developmental disorder, which has been reviewed previously ( Engel et al, 2010 , 2015 ; Webster, 2018 ). In aged mice, the agrin-LRP4-MuSK-AChR signaling pathway is implicated in aging-associated NMJ deficits ( Zhao et al, 2018 ). LRP4 protein levels are decreased in aged muscles and restoring the levels of LRP4 by transgenic expression or stabilization with sarcoglycan alpha maintained NMJ innervation, alleviated AChR fragmentation, and improved synaptic transmission ( Zhao et al, 2018 ).…”
Section: Comparison With Other Diseases That Affect the Nmjmentioning
confidence: 99%
“…In aged mice, the agrin-LRP4-MuSK-AChR signaling pathway is implicated in aging-associated NMJ deficits ( Zhao et al, 2018 ). LRP4 protein levels are decreased in aged muscles and restoring the levels of LRP4 by transgenic expression or stabilization with sarcoglycan alpha maintained NMJ innervation, alleviated AChR fragmentation, and improved synaptic transmission ( Zhao et al, 2018 ). Furthermore, viral-mediated upregulation of DOK7 in aged mouse muscle significantly enhanced motor function, muscle strength, NMJ innervation, and compound muscle action potential amplitudes ( Ueta et al, 2020 ).…”
Section: Comparison With Other Diseases That Affect the Nmjmentioning
confidence: 99%